Strategi Komunikasi Yayasan Puteri Indonesia Dalam Memperkuat Hubungan Dengan Media Untuk Menjaga Citra Positif - Wulandari, Sri (Brand Communication, 2023)
Yayasan Puteri Indonesia (YPI) is an organization that oversees the Puteri Indonesia beauty pageant. First organized in 1992, it is routinely held every year. Puteri Indonesia Foundation has a Communications department to publicize all its activities. Puteri Indonesia Foundation has held many events related to media relations. Relations with the mass media are needed to publicize activities related to the selection of Princess Indonesia. The method used in this research is a qualitative method with a case study approach to reveal the communication strategy of the Puteri Indonesia Foundation in dealing with the media. Data collection is based on interviews, observation and documentation. The results of the study answer the objectives to be achieved. The communication strategy used by the Puteri Indonesia Foundation with the media uses a personal or informal approach. Puteri Indonesia Foundation places media people as partners. The good relationship benefits the Puteri Indonesia Foundation, the news about the activities of the Puteri Indonesia Foundation can be well received by the public